An investigation of the school literacy programs at State Senior High School 4 in Banda Aceh - Rocky Harisman Saputra (Universitas Syiah Kuala, 2021)
This research aims to investigate a literacy program at a senior high school level. The researcher obtained the data for this research from Senior High School 4 in Banda Aceh because it has a better English teaching and learning process, and the school implemented a specific literacy program. The participants involved in this research include the school principal, vice school principals, the head of the school library, teachers, and 20 students from science and social science classes. The data in this research was collected using an observation sheet and interview guide to evaluate the literacy program based on the CIPP framework. The research results show that the literacy program at the school includes learning strategies provided by the teacher, the availability of facilities, and student reading interest. Based on the interview results, students were not motivated to participate in the school literacy program. Therefore, it is suggested that specific policy needs to be made and reinforced in order to implement a literacy program at senior high schools.